Worker signals among new college graduates: The role of selectivity and GPA - Brad J. Hershbein (W.E. Upjohn Institute for Employment Research, 2013)
Recent studies have found a large earnings premium to attending a more selective college, but the mechanisms underlying this premium have received little attention and remain unclear. In order to shed light on this question, I develop a multidimensional signaling model relying on college grades and selectivity that rationalizes students' choices of effort and firms' wage-setting behavior. The model is then used to produce predictions of how the interaction of the signals should be related to wages, namely that the return on college GPA should fall the more selective the institution attended. Using five data sets that span the early 1960s through the late 2000s, I show that the data support the predictions of the signaling model, with support growing stronger over time as college sorting by ability has increased. The findings imply that return to college selectivity depends on GPA, something previously not recognized in the literature, and they can rationalize why employers learn more quickly about college graduates' productivity than less educated workers'.
Keywords: I20; I21; J31; 330; college graduates; signaling; school quality; grade point average